Relationships of mental budgeting of the self-employed without personnel with tax compliance, pension, and disability arrangements - Antonides, Gerrit; de Groot, I. Manon (Frontiers in Behavioral Economics, 2024)
Self-employed people without personnel mostly behave like consumers in managing their business finances, frequently leading to ill-management of the company finances. Ill-management may lead to inability to fulfil important financial obligations and making financial arrangements for the future.Here, we investigate the hypothesis that financial management indicators (e.g., overview of expenses, making ends meet) are related to four measures of tax compliance, i.e., the OECD measure of tax compliance, measures taken by the tax administration, enforced tax compliance, and voluntary tax compliance, and two measures of social security: pension and disability arrangements. Since mental budgeting may facilitate financial management, it may either be directly related to tax compliance and social security arrangement indicators or indirectly through financial management. We use survey data from a sample of 1,191 Dutch self-employed people without personnel, roughly equally divided between starters (≤ 3 years in business) and non-starters (> 3 years in business). We found both significant direct and indirect effects of mental budgeting on tax compliance and social security arrangements, thus showing incomplete mediation effects of financial management.Managing money has been an important topic of research in economic psychology because illmanagement may lead to incapacity to fulfil one's financial obligations, not making ends meet, and even problematic debts (e.g.